TRANSFORMATION OF CURRICULUM PGMI S-1 UIN SUNAN KALIJAGA YOGYAKARTA INTO A MODEL CURRICULUM MERDEKA BELAJAR KAMPUS MERDEKA (MBKM) - Suleman, Muh. Asharif; Idayanti, Zulfi; Basri, Basri; Hilmi, Ahmad (PIONIR: JURNAL PENDIDIKAN, 2024)
This research aims to study the independent campus curriculum PGMI S-1 UIN Sunan Kalijaga Yogyakarta, which refers to KKNI, SNPT, Integration-Interconnection, and Merdeka Campus. This research includes descriptive and qualitative approaches, namely decrypting the MBKM curriculum on PGMI S-1 UIN Sunan Kalijaga Yogyakarta. The data used is a final curriculum document for Merdeka Campus PGMI S-1 UIN Sunan Kalijaga Yogyakarta for the year 2020, which is accessed on the official website https://pgmi.uin-suka.ac.id and supported by literature that is sourced from national and international indexed books and journals that contain topics on the development of the MBKM production PGMI curriculum. The results of the research show that the PGMI Prodi S-1 UN Sunan Kalijaga of Yogyakarta already has policies and guidelines for implementing structured MBKM activities. The activities adapt the characteristics of the PGMI product and are dissocialized offline and online.Keywords: Curriculum model, Education, MBKM, PGMI